Pathophysiology of epileptic seizures. Issue Volume 36:Issue S1(2014) (1st September 2014) - Penderis, Jacques
Abstract : Epilepsy represents the most common chronic neurological condition in the dog. As our understanding of the underlying pathophysiology improves, we are better able to describe the neuroanatomical diagnosis, select the best medication for an individual patient and predict the potential for pharmacoresistance to antiepileptic drugs (AEDs). An epileptic seizure is a clinical sign of neurological disease (similar to any other neurological abnormality, such as ataxia or paresis), whereas epilepsy is defined as recurrent epileptic seizures (ie, a patient does not have epilepsy until it has had repeated seizures). Epileptogenesis is the process whereby a seizure focus develops or increases in size, with an associated increase in seizure frequency or severity. While the effect of early instigation of treatment with AEDs on epileptogenesis is still to be elucidated, it is apparent that early treatment results in the development of less long term adverse behaviour effects in the patient. The main risk factors for pharmacoresistance to AEDs include breed (in particular the border collie) and severe or progressively worsening seizures.